ANALISIS POLA PERKEMBANGAN HARGA DAN PENENTUAN POSISI JUAL ATAU BELI JAGUNG DIPASAR BERJANGKA JEPANG - Antik Suprihanti (Jurnal Dinamika Sosial Ekonomi, 2009)
The analysis of Price Growth Pattern and Taking Position Sell or Buy at Corn Future Market in Japan. the research aim to brow corn daily price growth pattern from januari until October 2007, taking of position at corn future Market in Japan and analysis posittion and situation of corn in Indonesia in term of corn future market. Research Method used descriptive analysis. Kinds of data uses secondary data. Data sources obtained of Tokyo Grain Exchange (TGE), Laboratory of Galeri invesment (LGI) which cooperate with PT. Asia Kapitalindo in UGM.  Badan Pengawasan Berjangka Kembali (BAPPEBTI), book study, and internet. Taking of position sell or buy, is conducted by fundamental and technical analysis. Result show that corn daily price from Januari until October 2007 following long-range price trend pattern, seasonally and random. Buying position if the price trend to up and selling position if the price trend to down to minimize the risk. Demand of lndonesia corn is increasing but the production always decreasing, so the goverment must import corn.Keywords:  Future Market, Corn, Possition. Growth pattern